Conditions for effectiveness of prompts in solving challenging problems of artistic and scientific content - Anna A. Matyushkina; Marina I. Kunashenko (Saratov State University, 2021)
The study analyzes the problem of the influence of prompts on the achievement of creative problem solution and conditions under which it is effective. The relevance of the topic is determined by the context of the determinants and factors that define success of solving creative problems. From the standpoint of the problem situations theory, we revealed conditions for positive influence of direct and indirect prompts in solving problems of different content. Various characteristics of the subject of thinking are considered as conditions: from the perspective of the intellectual sphere, it is general intelligence and depth of analysis, while from the perspective of motivational sphere, it is manifestation of situational cognitive need, from the perspective of personality sphere, these are characteristics associated with the task content. The purpose is to study conditions for effectiveness of prompts in solving problem situations of different content. We propose the hypotheses stating that conditions for effectiveness of prompts are: manifestation of interest in solving challenging problems of any content; intellectual characteristics when solving scientific problems; personal characteristics when solving artistic problems. The sample consisted of 39 people: 27 students of the 1st and 2nd year of the Faculty of Psychology from Moscow State University and 12 specialists in the problem field. It also involved representatives of other professional fields, who carried out expert assessment of the effectiveness of prompts. The participants of the study solved 8 challenging problems of scientific and artistic content with prompts, 216 solution protocols were analysed. We used the following techniques: "Progressive matrices of Raven" and "Complex analogies" for diagnostics of intellectual features; the technique of self-actualization of personality for personality sphere diagnostics; subjective scaling for diagnostics of the assessment of interest manifestation. It is shown that subjective conditions for the effectiveness of the prompt are different depending on the content of the problem and on its difficulty for the subject. For most problematic situations of scientific content, a direct prompt turns out to be significant, and the condition for its effectiveness is the manifestation of the subject's interest in the solution. For difficult problematic situations of artistic content, the depth of analysis, general intelligence and personal characteristics of the subject, which are associated with understanding the content of the problem, are the conditions for the effectiveness of indirect prompts.